Told Round a Brushwood Fire - Arai, Hakuseki, 1657-1725 (UNESCO collection of representative works. Japanese series., 2014)
The Oritaku Shiha no Ki of Arai Hakuscki (1657-1725) was the first Japanese autobiography and is often singled out as the most outstanding. As primary source material for the first half of the Tokugawa period, it constitutes a unique historical supplement to the official records. Presented here is a scholarly English translation of and commentary on this important work.